2018
DOI: 10.1016/j.ebiom.2018.10.006
|View full text |Cite|
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is activated in post-ischemic kidneys to promote chronic kidney disease

Abstract: BackgroundAcute kidney injury (AKI) may lead to the development of chronic kidney disease (CKD), i.e. AKI-CKD transition, but the underlying mechanism remains largely unclear. Endoplasmic reticulum (ER) stress is characterized by the accumulation of unfolded or misfolded proteins in ER resulting in a cellular stress response. The role of ER stress in AKI-CKD transition remains unknown.MethodsIn this study, we examined ER stress in the mouse model of AKI-CKD transition after unilateral renal ischemia-reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 50 publications
5
98
0
Order By: Relevance
“…Unilateral renal IR was operated as before. 44 Briefly, after anesthesia with pentobarbital (50 mg/kg, i.p. ), mice were kept on a Homeothermic Blanket Control Unit (Harvard Apparatus Ltd., Holliston, MA) to monitor and maintain body temperature at w36.5 C. The left renal pedicle was exposed by flank incision for unilateral clamping to induce ischemia for 30 minutes.…”
Section: Overactivation Of B-catenin Signaling Has Been Associatedmentioning
confidence: 99%
“…Unilateral renal IR was operated as before. 44 Briefly, after anesthesia with pentobarbital (50 mg/kg, i.p. ), mice were kept on a Homeothermic Blanket Control Unit (Harvard Apparatus Ltd., Holliston, MA) to monitor and maintain body temperature at w36.5 C. The left renal pedicle was exposed by flank incision for unilateral clamping to induce ischemia for 30 minutes.…”
Section: Overactivation Of B-catenin Signaling Has Been Associatedmentioning
confidence: 99%
“…113,[135][136][137][138][139][140][141] It is well established that ER stress pathways are activated in fibrotic renal disease, including in diabetic nephropathy and in ischemia, and that chemical chaperones such as 4-phenylbutyrate and tauroursodeoxycholic acid have been shown to reduce ER stress and result in fibrosis in animal models of renal disease. [142][143][144][145][146][147][148][149] It is unclear how TSP1 and other TSP family members might be participating in the UPR and other branches of the ER stress response and whether intracellular TSP1 functions are involved in fibrogenic processes. Studies on mutant COMP (TSP5) in models of pseudoachondroplasia showed a more severe phenotype in animals in which the mutant protein was expressed than in knockout mice.…”
Section: Intracellular Tsp1 As An Er Stress Regulator Of Ecmmentioning
confidence: 99%
“…Moreover, a clinical study on patients with renovascular complications reported an association of type 1 diabetes with polymorphism of MIOX gene, which underscores its clinical significance in the pathobiology of DN (31), although a comprehensive analysis of the events responsible for the MIOX-ROS-mediated tubulointerstitial injury in DN needs to be included in experimental animal models. Besides ROS, endoplasmic reticulum (ER) stress has also been implicated in the pathogenesis of diabetes, obesity, AKI, and chronic kidney disease (7,9,(32)(33)(34)(35). Whether MIOX worsens ER stress in DN remains to be explored.…”
mentioning
confidence: 99%